2018
DOI: 10.1002/jgc4.1052
|View full text |Cite
|
Sign up to set email alerts
|

Patient goals, motivations, and attitudes in a patient‐driven variant reclassification study

Abstract: Family studies to reclassify clinically ascertained variants of uncertain significance (VUS) can impact risk assessment, medical management, and psychological outcomes for patients and their families. There are limited avenues for patients and their families to actively participate in VUS reclassification, and access to family studies at most commercial laboratories is restricted by multiple factors. To explore patient attitudes about participation in family studies for VUS reclassification, we conducted semis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Our findings indicate that relatives had varied and nuanced experiences with patient‐driven familial VUS reclassification studies. Relatives share similar motivations with probands for participating in the VUS reclassification study, including a desire to increase knowledge about the variant and help their families and scientific researchers establish a link between the variant and their familial disease (Makhnoon et al, ; Tsai et al, ). Discussion of genetic information can open up health communications without impacting stress and anxiety levels, medical care, and behavior.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings indicate that relatives had varied and nuanced experiences with patient‐driven familial VUS reclassification studies. Relatives share similar motivations with probands for participating in the VUS reclassification study, including a desire to increase knowledge about the variant and help their families and scientific researchers establish a link between the variant and their familial disease (Makhnoon et al, ; Tsai et al, ). Discussion of genetic information can open up health communications without impacting stress and anxiety levels, medical care, and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Eligible participants for the interviews were English‐speaking adults (18 years or older) who had enrolled as a relative of a family member in the FindMyVariant study (Makhnoon et al, ; Tsai et al, , ), a patient‐driven study for reclassification of VUS in hereditary cancer genes. Individuals were asked to participate in the FindMyVariant study by a family proband, defined as a family member found to have one or more VUS through clinical testing who had contacted the FindMyVariant study for further VUS reclassification efforts (Tsai et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations